The terminal - Spielberg, Steven ([Australia] Paramount, 2014)
Viktor is a simple man with a mission, who finds himself entrapped in JKF airport after the accidental loss of his country to villainous coup. He becomes a man without a country, and is stuck in at the airport's international terminal with no visa, and is instructed that he is not allowed to leave. Slowly he encounters airport workers who come to his aid by mutual coercion. Gupta the hilarious Indian custodian; Enrique who transports food; Torres the security clerk and Mulroy. Viktor eventually falls for a stewardess who has spent her life waiting for the right man to come along.
Keywords: Man-woman relationships -- Drama